(untitled) (Docentes 2.0 Journal, 2020)
The objective of this essay is to reveal what are the harmful effects for people who must comply with an isolation either forced, by their own decision or by different types of diseases that directly or indirectly see the brain. Since 1970, the American Neuroscientist and Physiologist Mac Lean, developed the idea of ??the "triune brain", in which he locates three levels of brain structures: reptilian or instinctive brain. Although the brain has different anatomical and functional characteristics, they function as a "whole" when it comes to defining some type of response emanating from the brain and that affects the socio-emotional life of individuals. In the middle of the last century, the psychologist Maslow, elaborated the famous “Maslow pyramid” and Carter (1998) establishes that the first purpose of the human brain is to achieve survival, which is in line with the base of Maslow’s pyramid. When the Brain, through its five senses, detects that it cannot “maintain survival”, it enters what is called “a state of alert or threat”. This threat can be real or imagined, and the brain cannot distinguish one from the other. In addition, this does not refer only to "being hungry or thirsty", but also, "loneliness, isolation, not social contact", also perceived as a state of alarm and then we speak of a "stressed brain", which generates behaviors and habits harmful to people’s health, even suicides.